Alkaline Activated Coal Bottom Ash as Partial Cement in Mortar - Abu Kasim, Nurul Nabilah; Mokhatar, Shahrul Niza (Recent Trends in Civil Engineering and Built Environment, 2024)
In Malaysia, despite the carbon reduction plans, carbon dioxide (CO2) emissions and the associated rick of climate change are a cause of major concern. CO2 emissions due to cement manufacturing is pressing issue as well. In addition, there is a raising concern due to excessive of Coal Bottom Ash (CBA) from coal plants. The aim of this study is to examine the properties of different percentages of CBA as partial cement in mortar. To enhance the properties of alkaline activated CBA, a suitable mixture or percentage of CBA which were 0%, 20%, 40% and 60% with 0%, 2%, 4% and 6% of CaCl2 respectively were determined. To investigate the physical properties of the CBA, specific gravity test was conducted according to ASTM D792 and particle size analysis (PSA) was done according to ASTM D422-63. The performance of the mortar was being assessed via hardened properties testing such as compressive strength according to ASTM C496 with 36 samples of cubes and split tensile strength test according to ASTM C39 with 24 samples of cylinders were being conducted. It is hypothesized that the mixture of alkaline activated CBA in mortar improved its performance. The compressive strength of 40% of alkaline activated CBA was higher than the other mixture while the controlled samples still get the highest strength compared to the other mixtures and the split tensile strength of 40% of alkaline activated CBA increased compared to the other mixtures which shows decreased at the age of 7 and 28 days. The optimum mixtures of alkaline activated CBA were 40% and it proved that the mixtures could improve the strength of mixtures. Well designed and tested mortar mixture were contributed towards the strength aspects of this prospective green construction material. In conclusion, the research was starting the fundamental overview to design eco-friendly construction material and seek purpose to reduce pollution, decrease the landfill waste and help protect the natural resources.